2003
DOI: 10.1093/jnen/62.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Tau and Alpha-Synuclein Epitopes in Lewy Bodies

Abstract: The major protein constituent of Lewy bodies (LBs), the pathological hallmark of Parkinson disease and dementia with Lewy bodies, is considered to be alpha-synuclein, but other proteins, in particular the microtubule-associated protein tau, have been implicated in the pathogenesis of LBs. Tau is the major structural component of neurofibrillary tangles (NFTs). Both direct immunochemical studies of partially purified LBs and indirect immunohistochemical studies have suggested that LBs may contain tau, but most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
235
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(247 citation statements)
references
References 40 publications
9
235
2
1
Order By: Relevance
“…Higher burden of both -synuclein (Duda et al, 2002a;Jellinger and Attems, 2006) and amyloid-b deposition (Jellinger and Attems, 2006;Edison et al, 2008;Kalaitzakis et al, 2008) has been observed in the striatum of patients with DLB, suggesting a possible interaction between -synuclein and amyloid-b aggregation. Furthermore, tau and -synuclein deposits may be aggregating topographically in close proximity in synucleinopathies (Duda et al, 2002b;Ishizawa et al, 2003;Kotzbauer et al, 2004), supporting direct cross-seeding between the two types of pathologies (Guo et al, 2013), which could influence striatal degeneration in DLB patients.…”
Section: Discussionmentioning
confidence: 93%
“…Higher burden of both -synuclein (Duda et al, 2002a;Jellinger and Attems, 2006) and amyloid-b deposition (Jellinger and Attems, 2006;Edison et al, 2008;Kalaitzakis et al, 2008) has been observed in the striatum of patients with DLB, suggesting a possible interaction between -synuclein and amyloid-b aggregation. Furthermore, tau and -synuclein deposits may be aggregating topographically in close proximity in synucleinopathies (Duda et al, 2002b;Ishizawa et al, 2003;Kotzbauer et al, 2004), supporting direct cross-seeding between the two types of pathologies (Guo et al, 2013), which could influence striatal degeneration in DLB patients.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, as these proteins may co-aggregate and/or regulate each other [29,30,[159][160][161], immunization against one of them could reduce the aggregation or toxic modification of the others. For example, immunization against Aβ might be helpful at reducing α-syn and tau if administered at early disease stages [62]; likewise, α-syn antibodies might also be helpful in AD [162], and immunization against tau might be useful for PD [161,163]. In this sense, identifying and targeting polyvalent antigens or using single-chain polyvalent antibodies targeting simultaneously Aβ, tau, and α-syn could have synergistic effects, as it occurs with polyvalent vaccines for certain cancers and infections [164,165].…”
Section: Developing New Technologies For Immunotherapymentioning
confidence: 99%
“…The P301L FTDP-17-related form of tau is particularly pathogenic as it exhibits accelerated filament formation in vitro (Nacharaju et al, 1999) and transgenic mice expressing P301L tau develop neurofibrillary tangles (NFTs; Lewis et al, 2000). While idiopathic PD is not associated with NFTs, tau has been demonstrated in a subpopulation of Lewy bodies (Ishizawa et al, 2003). Using a viral vector for P301L tau, we previously developed a rat model for NFT formation in the basal forebrain (Klein et al, 2004).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%